Systemic Fraud and Toothless Audits: A Crisis of Public Trust in Indonesia - Mohamad Djasuli; Siti Yunia Amalia; Dilla Rachma Ayu; Firdaushil Hasanah (International Forum of Researchers and Lecturers, 2025)
This article employs a Critical Literature Review (CLR) approach, analyzing studies from 2013–2025 that include academic papers, nationally accredited journals (Sinta 2–4), and reputable international journals indexed by Scopus (Q1–Q4) to understand systemic fraud and audit failure in Indonesia.Previous re-search has mostly explained fraud from individual or organizational views, while few have addressed structural factors such as the normalization of fraud, weak regulatory oversight, and the crisis of auditor legitimacy. The synthesis reveals four main issues. First, systemic fraud in Indonesia has shifted from in-dividual misconduct to a structured socio-economic phenomenon rooted in culture. Second, auditing as a control mechanism remains technically focused, often failing to uncover collusive fraud involving top management. Third, an expectation gap exists between unqualified audit opinions and public demands for assurance against corruption, reducing trust in auditors. Fourth, conflicts of interest arising from audit fee dependence, weak regulation, and limited adoption of audit technology and forensic analytics indicate the need for institutional reform. Therefore, this article calls for an integrative framework that connects individual, organizational, regulatory, and socio-cultural dimensions to address systemic fraud and rein-force public accountability in Indonesia.